The Relationship between Effective Communication and Construction Risk Management among Kuantan Malaysian Construction Industries - Nur Fazlina, Abdul Rahman; Adeleke, A. Q. (Penerbit Akademia Baru, 2018)
In this paper, the influence of effective communica tion in construction risk management among Kuantan Malaysian construction industries was assessed. Then a survey was conducted on pilot test among 10 local c onstruction industries in Kuantan Malaysian, using stratified random sampling, out of which 10 questionnaires were collected for data analysis. Methodologically, this research is perhaps the first to study the influence of effective communication on construction risk management among Kuantan Malaysian construction industries. Us ing the five point Likert scale categories of risk management from previous studies. Pearson Correlation anaylysis output results affirmed that there is a strong positive relationship between effective communication and construction risk management among Kuantan construction industries.